Intersectionality Between Race and Gender - Wiggins, Sarah K. (My University, 2020)
It is known that gender and race discrimination are prominent problems in our society. They’re also heavily intertwined and studying the intersection of these two types of discrimination will help in understanding the complexity of the prejudices these individuals face. Gender refers to the symbolism of masculinity and femininity in the context of cultural and social differences rather than biological sex differences. This term can also be applied when describing a range of identities that are not limited to male and female, such as cisgender, intersex, or genderqueer. Race is a concept that groups people into categories based on distinguishing social and physical characteristics and qualities. These are both social constructs in which our society gives us identity but, unfortunately, these identities make way for labeling and stereotyping. This research will be examining the intersectionality of gender and race and how each of these interacts to disadvantaged individuals. This project will focus on the gender roles within African American, Asian American, and Caucasian males and females and will compare and contrast the different obstacles they face. Ultimately, the goal of this project is to shed light on the oppression these individuals face due to their differences in race and gender.